2019
DOI: 10.22146/farmaseutik.v15i2.47911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi dan Evaluasi Kesesuaian Penggunaan Antibiotik pada Pasien dengan Infeksi Methicillin Resistant Staphylococcus Aureus di RSUP Dr. Soeradji Tirtonegoro Klaten

Abstract: Methicillin Resistant Staphylococcus aureus (MRSA) menjadi masalah kesehatan terkini di dunia terkait angka morbiditas dan mortalitas yang tinggi. Pola resistensi bakteri juga mengalami perubahan dari waktu ke waktu sehingga diperlukan data yang sistematis mengenai prevalensi dan pola kepekaan bakteri S. aureus untuk mencegah resistensi dan mendapatkan outcome klinik yang baik. Tujuan Penelitian ini adalah untuk mengetahui prevalensi MRSA dan kesesuaian penggunaan antibiotik terhadap outcome klinik pasien di R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
9
0
3
Order By: Relevance
“…This study showed that male MRSA patients were 583 or 9.4% (range 32.5% -71.4%). The previous research supports the result of this study that there were more male MRSA patients (69.6%) [5]. It can be affected by several factors, such as poor hand hygiene rates in the male population compared to the female population, and it is also influenced by the hormone possessed by the female population, namely estrogen, which may affect the virulence factor Staphylococcus aureus bacteria [25].…”
Section: Mrsa Patients' Characteristicsupporting
confidence: 85%
See 1 more Smart Citation
“…This study showed that male MRSA patients were 583 or 9.4% (range 32.5% -71.4%). The previous research supports the result of this study that there were more male MRSA patients (69.6%) [5]. It can be affected by several factors, such as poor hand hygiene rates in the male population compared to the female population, and it is also influenced by the hormone possessed by the female population, namely estrogen, which may affect the virulence factor Staphylococcus aureus bacteria [25].…”
Section: Mrsa Patients' Characteristicsupporting
confidence: 85%
“…Another study also conducted in Trivandrum, India, in 2018 showed that all MRSA isolates were sensitive to the linezolid and vancomycin [4]. In Indonesia, an analytical study conducted in 2019 showed that the antibiotic chloramphenicol is very sensitive for MRSA, although it is not under therapeutic guidelines for MRSA [5].…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil penelitian 2 sebelumnya prevalensi infeksi Methicillin Resistant Staphylococcus Aureus (MRSA) yang dilaksanakan di RSUP Dr. Soeradji Tirtonegoro Klaten, menunjukkan bahwa terjadi peningkatan infeksi dari periode 2015 hingga 2018. Peningkatan yang terjadi yaitu 7,69% di tahun 2015, 5,63% di tahun 2016, 10,81% di tahun 2017 dan 12,94% di tahun 2018 [2].…”
Section: Pendahuluanunclassified
“…Staphylococcus aureus is a gram-positive facultative anaerobic bacterium that acts as a commensal organism and an important opportunistic pathogen for humans, which can cause bacteremic sepsis, endocarditis, pneumonia, osteomyelitis, arthritis, and skin diseases [1][2][3][4]. A study in Dr. Soeradji Tirtonegoro's hospital revealed that isolates were resistant to tetracycline antibiotics (64.8%), erythromycin (53.7%), and cloxacillin (40.7%) [5].…”
Section: Introductionmentioning
confidence: 99%